Distribution of HPV-16 variants among isolates from Paraguayan women with different grades of cervical lesion - Mendoza, Laura Patricia (2013)
Fil: Mendoza, Laura. National University of Asunción. Department of Public Health and Epidemiology. Health Sciences Research Institute; Paraguay.